PENGARUH BRAND AWARENESS DAN CELEBRITY ENDORSER TERHADAP REPURCHASE SEPEDA MOTOR YAMAHA MELALUI KEPUASAN PELANGGAN (STUDI PADA KONSUMEN DEALER YAMAHA MATARAM SAKTI SETIABUDI, SEMARANG) - Muhammad Ashar Fais; Naili Farida (Universitas Diponegoro, 2017)
The research was motivated by the use of motorcycle transportation in Indonesia is currently experiencing significant growth until Indonesia became a target potential for the company’s branded motorcycles around the world. Yamaha is one of the popular motorcycles brand in Indonesia because the quality has been recognized by the majority of the people of Indonesia. However, in the period 2013 to 2015 the bulk sales of Yamaha brand motorcycle in Indonesia, especially the Yamaha Mataram Sakti Setiabudi Semarang, experienced a decline in sales. Evaluation can be done probably with more enhanced back consumer brand awareness factor to the Yamaha brand motorcycles and with the use of the celebrity services who are well known by the public and are also able to provide information about the product in detail so expect costumers will be more satisfied and interested to re-purchase.The purpose of this research is to know the influence between brand awareness and celebrity endorser towards repurchase through customer satisfaction. This research type is explanatory research, data collection through questionnaires and interviews. The amount of samples in this research were 100 respondents by using purposive sampling technique. This research uses qualitative and quantitative analysis techniques. Quantitative analysis uses validity test, reliability test, crosstabs analysis, correlation coefficient, regression analysis of the two stages, the coefficient of the determination and test of significance (t-test and F-test).The results of this research approved that brand awareness (X1) and celebrity endorser (X2) affects customer satisfaction (Y1) and customer satisfaction (Y1) affect the repurchase (Y2). Based on the results of a two-stages regression, the customer satisfaction (Y1) variable’s has the most dominant influence.Based on the research results, the researcher suggest that the company has to provide a wide range of innovations in increasing brand awareness the customers to the Yamaha motorcycles brand, developing back the marketing advertising concepts on the use of the celebrity service and increasing the quality product of the Yamaha motorcycles to suit the customers expectations so that customers will be satisfied and have the desire to repurchase the Yamaha motorcycles.